2015
DOI: 10.1139/cjfas-2014-0400
|View full text |Cite
|
Sign up to set email alerts
|

The river as a chemostat: fresh perspectives on dissolved organic matter flowing down the river continuum

Abstract: Abstract:A better understanding is needed of how hydrological and biogeochemical processes control dissolved organic carbon (DOC) concentrations and dissolved organic matter (DOM) composition from headwaters downstream to large rivers. We examined a large DOM dataset from the National Water Information System of the US Geological Survey, which represents approximately 100 000 measurements of DOC concentration and DOM composition at many sites along rivers across the United States. Application of quantile regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
285
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 276 publications
(326 citation statements)
references
References 73 publications
23
285
8
Order By: Relevance
“…Meanwhile, we also found that contributions from tributary dilutions on DOC decreases were all positively correlated with water discharge in both river sections (Figures 4A,B). This relationship matched well with the fact that DOC concentrations and water discharge are generally positively correlated in most tributaries of the Mississippi watershed (Irena et al, 2015). Using the above mass balance approach, our results showed that tributary inputs are the primary control on riverine DOC longitudinal changes, while in situ processing play a secondary role.…”
Section: Tributary Inputs As a Dominant Control On The Doc Longitudinsupporting
confidence: 83%
“…Meanwhile, we also found that contributions from tributary dilutions on DOC decreases were all positively correlated with water discharge in both river sections (Figures 4A,B). This relationship matched well with the fact that DOC concentrations and water discharge are generally positively correlated in most tributaries of the Mississippi watershed (Irena et al, 2015). Using the above mass balance approach, our results showed that tributary inputs are the primary control on riverine DOC longitudinal changes, while in situ processing play a secondary role.…”
Section: Tributary Inputs As a Dominant Control On The Doc Longitudinsupporting
confidence: 83%
“…Our analyses, based on the extensive USGS observational dataset, provide a systematic examination of DOC variability and the associated environmental controls at regional and national scales. We observed substantial changes in the role of different environmental factors for explaining variations in DOC concentrations across different water resource regions in the U.S., which testifies to the complexity of coupled-terrestrial aquatic carbon cycling [49,54]. Significant spatial variability in environmental factors resulted in region-specific environmental controls on DOC concentrations [53].…”
Section: Environmental Controls On Doc Concentrationssupporting
confidence: 52%
“…The high litter inputs combined with high decomposition rates favor the generation of DOC and explain the relatively high average DOC concentrations in the 2nd order rivers (Figure 3). For large rivers, terrestrial sources tend to be outweighed by instream processes due to differences in water depth, land cover types, and nutrient conditions, as compared with small streams [49]. The standard deviation for stations on 6th and higher order rivers is smaller than that for low order (order < 5) rivers, which may be caused by the relatively balanced DOC input and removal in downstream regions [50].…”
Section: Spatial Patterns Of Doc Concentrationsmentioning
confidence: 98%
See 1 more Smart Citation
“…While Swedish rivers have substantial water renewal along watercourses from the Scandes to the Baltic Sea (Muller et al, 2013), at such broad scales several environmental factors may modify element bioavailability through modification and differential uptake and remineralisation of C, N, and P. For example, bacterial processing (Creed et al, 2015), photodegradation (Bushaw et al, 1996) and reactive oxygen (Gao and Zepp, 1998) may influence organic matter degradation and changes in bioavailability over the long timescales encompassed by large river systems. In this regard, it is interesting to note that our estimates of short-term macro-nutrient bioavailability were similar for lakes and rivers, which suggest that possible differences in long-term macronutrient bioavailability across these very different sites did not seem to impact on the results determined under our specific laboratory conditions.…”
Section: Broad-scale Riverine Bdoc Bdn and Bdp Patternsmentioning
confidence: 99%